Psychopathology, adversity, and creativity diversifying experiences in the development of eminent African Americans. [article]. - Damian, Rodica Ioana; Simonton, Dean Keith
Symptoms associated with mental illness have been hypothesized to relate to creative achievement because they act as diversifying experiences. However, this theory has been tested on predominantly majority-cultures samples. Do tendencies toward mental illness still predict eminent creativity when they coexist with other diversifying experiences, such as early parental death, minority-status, or poverty? These alternative diversifying experiences can be collectively referred to as examples of developmental adversity. This conjecture was tested on a significant sample of 291 eminent African Americans who, by the nature of their status as long-term minorities, would experience more developmental adversity. Replicating majority-culture patterns, African American artists showed higher mental illness rates than African Americans, regardless of profession. Furthermore, mental illness predicted higher eminence levels only for the African American artists, an effect that diminished when controlling for developmental adversity. Because the latter predicted eminence for both artists and scientists, the ?madness-to-genius? link probably represents just 1 of several routes by which diversifying experiences can influence eminence. The same developmental ends can be attained by different means. This inference warrants further research using other eminent creators emerging from minority culture populations. - - (from the authors)
Keywords: Mental illness-Periodicals.; Developmental adversity-Periodicals.; Minority cultures-Periodicals.; Eminence-Periodicals.